PROSPEK DAN STRATEGI PENGEMBANGAN KOPI ARABIKA SPECIALTY KETINGGIAN SEDANG BERBASIS KAWASAN DI KABUPATEN JEMBER - Diah Puspaningrum; Titin Agustina (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
The aim of this study was 1) to determine the productivity and income level at medium height of Arabica specialty in Jember District; 2) to know the prospects and specialty Arabica coffee development strategy at medium height in Jember District. The research method use descriptive and analytical methods while determining the research area was purposive. Determination of the sample was simple random sampling and determination of the sample was purposive sampling by conducting in-depth interviews. The results showed that: 1) Productivity arabica coffee specialty at medium height in Jember is 1892.12 kg/ha, 2) The income of coffee farmers is Rp. 6,606,366.14 per ha, 3) cultivation of specialty arabica coffee at medium height Jember district in the position of white areas and strategies that can be implemented is to undertake capacity building of the shareholder institutions that is Forest Village Community Organization who cultivated arabica coffee.